DESIGN AND IMPLEMENTATION OF A PIEZOELECTRIC PEDESTRIAN-POWERED ENERGY HARVESTING SYSTEM FOR SUSTAINABLE URBAN INSTALLATIONS - Muhammad Qamarul Islam; Ruzlaini Ghoni; Mohd Tarmizi Ibrahim; Budi Nugroho (Teknika, 2025)
This project proposes integrating a pedestrian-powered system into a public installation to create a renewable energy source in urban environments. The system utilizes piezoelectric sensors embedded in the sidewalk to convert mechanical energy from footsteps into electrical energy, which is then used to power lights and display kinetic movement in the art installation. The main goal of this project is to provide a participatory, environmentally friendly, and sustainable solution in the form of an interactive artwork, while reducing dependence on conventional energy sources. Test results show that the greater the applied load, the higher the generated voltage. The lowest voltage recorded was 11.76 mV at a weight of 50 kg, while the highest voltage reached 315.16 mV at a weight of 90 kg, with an average voltage of 168.46 mV for the load range of 50–90 kg. These findings demonstrate that piezoelectric technology has great potential as an energy harvesting system in public areas, as it can provide power for energy-efficient devices while enhancing the aesthetic quality and awareness of sustainable energy in urban spaces.